2017
DOI: 10.1016/j.ydbio.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-exposed oocytes accumulate and transmit damaged mitochondria due to an inability to activate mitophagy

Abstract: Mitochondria are the most prominent organelle in the oocyte. Somatic cells maintain a healthy population of mitochondria by degrading damaged mitochondria via mitophagy, a specialized autophagy pathway. However, evidence from previous work investigating the more general macroautophagy pathway in oocytes suggests that mitophagy may not be active in the oocyte. This would leave the vast numbers of mitochondria - poised to be inherited by the offspring - vulnerable to damage. Here we test the hypothesis that inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 58 publications
5
51
0
Order By: Relevance
“…Our theory therefore suggests that inhibition of basal mitophagy may be able to slow down the rate of random genetic drift, and perhaps healthy aging, by locking-in low levels of heteroplasmy. Indeed, it has been shown that mouse oocytes (Boudoures et al, 2017) as well as mouse hematopoietic stem cells (de Almeida et al, 2017) have comparatively low levels of mitophagy, which is consistent with the idea that these pluripotent cells attempt to minimise genetic drift by slowing down mtDNA turnover. A previous modelling study has also shown that mutation frequency increases with mitochondrial turnover (Poovathingal et al, 2009).…”
Section: Targeting Mitophagy Rate Against Mutant Expansionssupporting
confidence: 60%
“…Our theory therefore suggests that inhibition of basal mitophagy may be able to slow down the rate of random genetic drift, and perhaps healthy aging, by locking-in low levels of heteroplasmy. Indeed, it has been shown that mouse oocytes (Boudoures et al, 2017) as well as mouse hematopoietic stem cells (de Almeida et al, 2017) have comparatively low levels of mitophagy, which is consistent with the idea that these pluripotent cells attempt to minimise genetic drift by slowing down mtDNA turnover. A previous modelling study has also shown that mutation frequency increases with mitochondrial turnover (Poovathingal et al, 2009).…”
Section: Targeting Mitophagy Rate Against Mutant Expansionssupporting
confidence: 60%
“…Annexin V is a marker of early apoptosis, and an increased level of annexin V indicates an abnormally high apoptotic level . Mitochondria are the factory that generates ATP, over‐aggregated mitochondria indicate impeded mitochondrial autophagy, and the cellular ATP level might decrease consequently . Our results showed that MPP6 depletion significantly elevated the ROS (Figure A,B, ROS level, Ctrl vs MPP6‐DE, 19.59 vs 37.68) and annexin V (Figure C,D, annexin V intensity, Ctrl vs MPP6‐DE, 15.53 vs 21.21) levels.…”
Section: Resultsmentioning
confidence: 63%
“…34 Mitochondria are the factory that generates ATP, over-aggregated mitochondria indicate impeded mitochondrial autophagy, and the cellular ATP level might decrease consequently. 35 Our results showed that MPP6 depletion significantly elevated the ROS (Figure 6A Figure 6E).…”
Section: Mpp6 Is Important For Oocyte Quality In Multiple Waysmentioning
confidence: 50%
“…The study reports that mtDNA haplotype influences mitochondrial proteostasis, metabolic syndrome and reactive oxygen species generation 29 . Mouse models suggest that metabolic syndrome is transmitted via mitochondria transgenerationally owing to defective mitophagy (destruction of mitochondria by the cell) 30,31 .…”
Section: Studies On Mitochondrial Donationmentioning
confidence: 99%